Coeliac disease – systematic review of origin, pathology, diagnosis and treatment - Puchalski, Krzysztof; Zwolski, Maciej; Szumlas, Zuzanna; Klocek, Konrad; Hajduk, Aleksandra; Jurek, Aleksander; Mrozek, Łukasz; Kostecki, Bartosz (Journal of Education, Health and Sport, 2023)
Introduction and Purpose: Coeliac disease is an increasingly prevalent disorder worldwide. It is estimated to affect about 1% of the population and its symptoms heavily impact people's lives. The aim of this paper is to delve into the topic of coeliac disease and present basic information about its origins, current diagnostic methods, and the challenges associated with its treatment. This article includes all the necessary information from up-to-date sources. State of Knowledge: Coeliac disease was discovered a long time ago, but it is still not completely understood. Every year, new research is published regarding different populations in various countries. While we know more about the disease, its symptoms, and causes, we are still far from fully understanding all the inflammatory processes occurring in the human body. There is solid evidence that this enteropathy is caused by gluten, and the only way to reduce the clinical manifestation of coeliac disease is to adhere to a gluten-free diet. However, some patients do not benefit from this type of diet and still suffer from coeliac disease. New drugs currently being developed offer hope for these individuals, as they attempt to target the immunological reaction and mitigate the immune response in the small intestine. Conclusion: As approximately 1% of the population suffers from this disease, it is crucial to diagnose patients in the early stages of its development. Early diagnosis can prevent the development of other disorders that coexist with coeliac disease, which can be particularly dangerous, especially for children. This paper provides up-to-date information about the clinical manifestations of the disease, as well as methods of diagnosis.